Who's to Blame? Effects of Perpetrator Gender and Victim Confrontation on Perceptions of Blame - Skrbec, Megan L.; Schneider, Carlee S. (My University, 2014)
The purpose of this study was to analyze participant's perception of blame and victimization based on the gender of the perpetrator and the presence of verbal conflict previous to the domestic abuse behavior.
Color poster with text and graphs.
Keywords: Domestic violence; Male perpetrator vs. female perpetrator--Perceptions; Posters